Schools that learn : a fifth discipline fieldbook for educators, parents, and everyone who cares about education - Senge, Peter M. (New York : Doubleday, 2000)
Explains how to develop and maintain schools that are consistently effective; includes real-world examples from teachers and administrators and covers philosophies and practices in the classroom, the school as a whole, and the community.
"A Currency book.".
"A fifth discipline resource.".
Includes bibliographical references and index.
Publisher's Weekly.
Adult
Keywords: Education -- United States; Organizational learning -- United States; School improvement programs -- United States; Education -- United States; School improvement programs